Safe Spaces or Brave Spaces?: Re-Envisioning Practical Theology and Transformative Learning Theory - Lamont, Tracey (Religious education, 2020)
The Loyola Institute for Ministry (LIM) developed a method of practical theology for ministry professionals and religious educators rooted in transformative learning theory to enable students to reflect more intentionally and theologically on their experiences in ministry. This study asks, by teaching students to engage in dialogue through transformative learning practices in safe spaces, are religious educators inhibiting the self-actualization needed to confront white normativity and expose white fragility, thus, advancing rather than dismantling racism with our students in graduate programs in ministry and religious education?